Prevalence and Analysis of Risk Factors for Cataracts in Jember Regency, Indonesia - Rohmah, Siti (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2024)
Introduction: Cataracts are the leading cause of preventable blindness. This study aims to determine the prevalence of cataracts and analyze the risk factors for cataracts in Jember Regency. Methods: The research design is observational research with a cross-sectional approach. The study carried out eye examinations on 1000 adults (≥50 years) who were randomly selected in Jember Regency. Risk factors analyzed included age, gender, education, occupation, smoking, and history of diabetes mellitus and hypertension. Results: The prevalence of cataracts in Jember Regency is 25.3%. Risk factors associated with the incidence of cataracts are age (OR=1.35; 95%CI: 1.02-1.98), female gender (OR=1.54; 95%CI: 1.12-2.13), low education (OR=1.83; 95%CI: 1.22-2.73), outdoor work (OR=3.72; 95%CI: 1.14-5.58), smoking (OR=1.42; 95%CI: 1.01-2.00), and history of diabetes mellitus (OR=2.15; 95%CI: 1.43-3.24). Conclusion: The prevalence of cataracts at ages ≥ 50 years in Jember Regency is quite high. Age, female gender, low education, outdoor work, smoking, and a history of diabetes mellitus are risk factors for cataracts.